Electron beam welding of CrMnNi-steels: CFD-modeling with temperature sensitive thermophysical properties. (August 2019) - Borrmann, S.; Kratzsch, C.; Halbauer, L.; Buchwalder, A.; Biermann, H.; Saenko, I.; Chattopadhyay, K.; Schwarze, R.
Highlights: Implementation of a comprehensive welding model into OpenFOAM. Temperature-sensitive properties have significant impact on the weld shape. Accurate implementation of latent heat of fusion leads to weld pool teardrop shape. Typical number of free parameters of the combined heat source was reduced. Keyhole and recoil pressure are calculated considering ambient pressure in EB chamber. Abstract: Applying and improving electron beam welded (EBW) joints to newly developed high-alloy TRIP/TWIP steels requires in-depth knowledge of the underlying physical phenomena. In an effort to further understand such phenomena, a CFD model is developed in the free, open source CFD software OpenFOAM. Its goal is to provide a basis for gaining deeper insight into the thermofluid-dynamical processes, which includes heating, melting, weld pool fluid dynamics, vaporization, solidification and cooling. For this purpose, a combined double-ellipsoid conical heat source (HS) is implemented into an existing finite volume solver to model the heat input of the electron beam (EB) into the weldment. As the HS is accompanied by a variety of free parameters, those parameters are adjusted to reproduce the shape of experimentally welded joints. Complete sets of parameters are presented accordingly. Furthermore, the thermophysical properties are implemented temperature-sensitive in order to account for the strong temperature gradients affecting heat transport. Since the solidified material is saved as an extra field in order to distinguish it from the parent metal, the seam geometry can be evaluated following the simulation. The resulting simulated weld cross section shows noteworthy good agreement compared to the experimentally obtained full penetration seam. Moreover, the typical teardrop shape of the weld pool is obtained in the simulations, so the usual approach of elongating the HS in its rear part is not necessary. Since the developed model is capable of reproducing the seam development during EBW, it could eventually be used to implement and investigate additional physical effects.